2012
DOI: 10.1159/000335823
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of a Cream Containing <i>Terminalia chebula</i> Extract

Abstract: Background: This study aimed to formulate a water-in-oil emulsion (formulation) of Terminalia chebula versus its vehicle (base) as control, and investigate its effects on skin melanin, skin erythema, skin moisture content, and transepidermal water loss (TEWL). Material and Methods: Base containing no active material, and formulation containing 5% concentrated extract of T. chebula, were developed. Different stability parameters were monitored at 8, 25, and 40 °C, as well as 40 °C + 75% relative humidity, for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…After skin treatment with water-in-oil emulsion based cream loaded with hydroalcoholic extract of Terminalia chebula plant for eight weeks, reduced transepithelial water loss was observed. Moreover, there was decrease in skin melanin contents also [ 60 ]. These features could be due to the phenolic compounds present in extract.…”
Section: Phytoextract Loaded Creamsmentioning
confidence: 99%
“…After skin treatment with water-in-oil emulsion based cream loaded with hydroalcoholic extract of Terminalia chebula plant for eight weeks, reduced transepithelial water loss was observed. Moreover, there was decrease in skin melanin contents also [ 60 ]. These features could be due to the phenolic compounds present in extract.…”
Section: Phytoextract Loaded Creamsmentioning
confidence: 99%
“…It has also been investigated in clinical studies for its antioxidant effects and reversing the effects of pollution-induced skin damage [33]. The water-soluble extract contains >60% hydrolysable tannins including chebulinic and chebulagic acids, both of which provide long-lasting antioxidant properties [34][35][36] and biological mechanisms, for example, anti-inflammatory and photoprotective effects, that prevent skin ageing and restore skintoning [37][38][39][40][41][42]. The photoprotective effects of Haritaki fruit extract have been demonstrated by others using normal human dermal fibroblasts (HDFs) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies support multiple skin benefits of extracts prepared from the fruit of TC, from antioxidant, anti-inflammatory and anti-microbial effects to depigmentation, wound healing and rejuvenating effects. [18][19][20][21] However, many of the studies were performed using crude extracts prepared with non-aqueous or aqueousalcoholic solvents. This lies in sharp contrast to the study described here and previously reported that utilized a TC fruit extract prepared from a well-defined aqueous process that reliably yields high levels of the bioactive phytochemicals known to account for its biological properties.…”
Section: Discussionmentioning
confidence: 99%